Post-Traumatic Stress Disorder Following Surgery: A Case Report of A Three-Year-Old Child with Deep Dermal Burn Injury - Hajeng Wulandari; Ariani (Pediatric Sciences Journal, 2022)
Introduction: In the past few years, there has been increased recognition that children, who have a history of traumatic incidences, can develop post-traumatic stress disorder (PTSD), just like in adults. Case: We presented a case of PTSD in a 3-year-old child hospitalized in the hospital for two days due to combustion (deep dermal burn injury) in his left hand, stomach, and both of his legs. The patient started to experience parasomnia such as nightmares, raves, difficulty to sleep and awakened from sleep (for one month from the beginning of wound treatment and debridement). The patient also had two re-experiencing symptoms: nightmare and emotional distress (anxiety, anger) after a traumatic stimulus. From his temperament scale and character assessment, there was dysregulation disorder. From the PEDSQL parent's reports, there was also decreased quality of life. Conclusion: First-line therapy of PTSD for the pediatric population is supportive psychotherapy with trauma-focused cognitive behavioral therapy (TF-CBT) that results in a remarkable improvement in child's psychiatric outcome.